Modelo de esquizofrenia induzido pelo priming de receptores D2: Influência do sexo e do estresse peripuberal - Santos Júnior, Manuel Alves dos (2018)
Schizophrenia is a severe and chronic mental disorder that affects the thinking, feeling and behavior of the patients. Characterized as a complex syndrome with a combination of heterogenous symptoms, is widely acknowledged to be a polygenic disorder with developmental and environmental factors mediating the probability of becoming a schizophrenic. One of the major pathophysiological findings in patients with schizophrenia is the increased sensitivity of the dopamine D2 receptor, with no change in the density of these receptors. Postnatal exposure to psychological trauma is a risk factor for developments in psychiatric disorders such as schizophrenia. Consistent evidence from several studies has identified childhood trauma as a putative risk factor for the development of schizophrenia. For a better understanding of the heterogeneity and complexity of the symptoms of schizophrenia, it is necessary to develop experimental models with greater translational validity. We aimed to investigate the behavioral and neurochemical changes in adult mice submitted to D2 receptor priming induced by neonatal quinpirole administration in addition to exposure to childhood stressful events. Male and female Swiss mice were treated with quinpirole (QNP 1 mg / kg; i.p.) during the postnatal day (PND) 3 to 13. Following exposure to stressful events in childhood (PND 22-32). The animals were divided into the following groups: saline (Sal); QNP; saline + stress in childhood (EST); QNP + EST for both male and female animals. In the DPN 50 the animals were submitted to tests of open field, elevated plus-maze, sociability and preference for social novelty and pre-pulse inhibition. After the tests were performed, the areas of the prefrontal cortex, hippocampus and striatum were dissected for analysis of the levels of monoamines. The results showed that the male and female animals submitted to D2 receptor priming presented hypolocomotion when compared to controls. Only males exposed to stress in childhood showed an increase in locomotor activity when compared to control animals. Sensitization by QNP affected the exploratory activity in females in relation to the saline group. The D2 receptor priming did not alter the stereotyped behavior profile of self-grooming in both sexes. Only in the group of males was there a decrease in these behaviors when exposed to stress added to the priming of D2. Both sexes, animals treated with neonatal QNP showed an increase in defecation compared to saline groups. The females showed a profile of hypolocomotion and increased defecation, suggesting that females submitted to D2 priming showed an increase in emotional response. In addition, animals submitted to D2 priming showed less anxiety-like behavior (males than females). Both were less sociable and had a PPI deficit. When exposed to both D2 receptor priming and childhood stress, the animals did not present the same set of changes or an exacerbation of the same. The females continued to exhibit hypolocomotion (the males had a lower exploratory activity). Females presented lower sociability and social memory deficits, while males did not present social deficit. Both had no PPI deficits. Taken together, our findings suggest that D2 receptor priming induces behavioral changes like schizophrenia when adults and there was an influence of gender. The females presented a behavioral profile similar to the affective component of schizophrenia. Males subjected to D2 receptor priming and exposed to stressful events in childhood presented schizophrenia-like symptoms, while females did not present. It is necessary to perform additional experiments to evaluate the neurobiological mechanisms studying this animal model.